Estrategia didáctica y su incidencia en la comprensión lectora en los estudiantes del noveno año de educación general básica de la unidad educativa “Dr. Néstor Mogollón López”, cantón La Maná, período lectivo 2021-2022. - Saca Plasencia, Nancy Maricela (2022)
The teaching of reading and its comprehension occupies a preponderant place within the study plans because it is the basis of the rest of the subjects, these processes deserve special attention within the school activity and also in society. Reading comprehension constitutes one of the main ways of prior knowledge through the combination of a lexical-syntactic and semantic process to assimilate reading. The objective of this research is to develop a didactic strategy for reading comprehension in ninth-year students of Basic General Education. This project was carried out in the Educational Unit Dr. Néstor Mogollón López of the La Maná Canton in the period 2019-2020. The design was approached through a qualitative-quantitative approach through descriptive, exploratory research with observation techniques, a survey that was applied to the population under study. In the results, it was observed that metacognition has a link with the basic understanding of 'learning to learn' in relation to the development of skills and improvement of assimilation; With the appropriation of reading, the teacher will be able to distinguish significant advances in learning and improve school performance in the area of Language and Literature. It is concluded that students will develop abilities, skills and reflective analysis in the perception of information when reading with trained teachers who will provide a quality and warm education at the upper basic level.